Exploration of doctoral students’ supervisory experiences in Pakistani universities - Zahid, Muhammad; Mahmood, Qaisar Khalid (Faculty of Social and Political Science, Universitas Airlangga, 2025)
Doctoral education and PhD completion are influenced by various factors, including student-related, institution, and supervisor. This study explores PhD scholars’ considerations in selecting supervisors and documents their experiences regarding accessibility, supervisory meetings, and feedback. PhD scholars from four universities were interviewed. The data were analyzed using the Braun and Clarke thematic analysis approach. The findings reveal that Pakistani PhD scholars meticulously select their PhD supervisor keeping in view research related factors, professional and personal factors of supervisors. Findings also show that PhD scholars emphasized alignment of research area, good fit, and accessibility for good and timely feedback particularly in cases where supervisory relationships may be characterized as toxic. PhD scholars had mixed supervisory experiences during their PhD study. Some PhD scholars deemed their supervisors as “ideal”; however, there were cases of toxic supervision. The study emphasizes the need for universities to provide academic assistance and guidelines, as well as to create a conducive environment for PhD scholars and supervisors by enhancing communication, support systems, and training opportunities. The study contributes to the understanding of these challenges and aims to provide insights for improving the doctoral education process in and beyond Pakistan.